Utilization of iron ore slime and bottom ash: An overview - Kumar R.; Mandal A.K.; Dishwar R.K.; Sinha O.P. (My University, 2025)
Steel plants are the primary producer of solid waste materials like slags from blast furnaces and L.D. Plant with fly ash /bottom ash from the power plant, iron ore slimes from ore washing plant, coal/coke from coke ovens, etc. It is estimated that about 84% of total solid waste generation is in iron ore tailings (Fines/ Slimes), coal combustion residues (Fly Ash or Bottom Ash), and the remaining 16% constitute all others, including slag. The above wastes (Iron ore slime & Bottom ash/ Fly ash) are being used for landfilling and in few countries to get value-added products. However, the partial or bulk utilization of such waste is still an academic issue in India. The present paper reviews past and recent research work to utilize two significant unutilized waste (Iron ore slime & Bottom Ash). The promising areas for utilization of Iron Ore Slime and Bottom Ash are the making of bricks (constructional, insulation), use as bed filter materials, and Ferro / master alloys' production as a part of metal recovery using smelting reduction process. (e.g., Al, Si, etc.). © 2021 Elsevier Ltd. All rights reserved.